The Concept of the “Scenario” Organized Business English Textbook - Boris V. Tarev (ARPHA Proceedings, 2021)
The article is devoted to the development of a business English textbook for students of an economic university using the “scenario approach”. The author analyzes the existing concepts of designing English textbooks, the application of the scenario method in various scientific and practical fields. The study proposes a set of requirements for a modern business English textbook as well as a scenario-based textbook model. The author focuses his attention on the list of skills and qualities that a student acquires when mastering Business English while participating in various situational and scenario contexts of professional activity. The article shows the process of formation and development of a future professional’s personal qualities while solving problematic tasks that underlie the training scenario. Practically significant are the types and examples of assignments that form a scenario in the structure of a business English textbook. Particular attention is paid to the problem of creating a context of intercultural business communication, reflecting the natural situations of interaction between business partners who communicate in English.